The Nervous System Development Regulator Neuropilin-1 as a Potential Prognostic Marker and Therapeutic Target in Brain Cancer - Eduardo Mello Rodrigues; Allan Fernando Giovanini; Carmen Austrália Paredes Marcondes Ribas; Osvaldo Malafaia; Rafael Roesler; Gustavo Rassier Isolan (2023)
Neuropilins are transmembrane glycoproteins that regulate developmental processes in the nervous system and other tissues. Overexpression of neuropilin-1 (NRP1) occurs in many solid tumor types and, in several instances, may predict patient outcome in terms of overall survival. Experimental inhibition of NRP1 activity can display antitumor effects in different cancer models. Here, we review NRP1 expression and function in adult and pediatric brain cancers, particularly glioblastomas (GBMs) and medulloblastomas, and present analyses of NRP1 transcript levels and their association with patient survival in GBMs. The case of NRP1 highlights the potential of regulators of neurodevelopment as biomarkers and therapeutic targets in brain cancer.